Pemanfaatan Teknologi Inforrmasi Dan Pencegahan Stunting Di Desa Burni Bius Baru, Kecamatan Silih Nara - Gemasih, Husna; Sentosa, Edi; Fasary, Wulan; Rezeki, Iryana; Sari, Fitri Sia Rifa; Putri, Yuni Sakinah; Selpiana, Widia; Gustina, Rike; Rusmawati, Rusmawati; Pratama, Yudha Saputra; Dermawan, Zikri Syah; Irama, Rhoma; Fitra, Deni Syah; Nate, Wein Pinte; Syahputra, Hamdan; Mahlidan, Mahlidan; Tirmiara, Iwan; Riadi, Riadi; Termulo, Rahmad; Qalbi, Wein Syahdi; Rahayu, Isnaini (Universitas Gajah Putih, Indonesia, 2023)
Real Work Lecture (Kuliah Kerja Nyata or KKN) is a form of community service aimed at improving the welfare and empowerment of the community through real activities. Thematic KKN students, in the context of their service, focus on the development and utilization of technology while actively participating in stunting prevention efforts. In the era of digitalization and modernization, nearly every aspect of daily life is connected to technology. Technology, when used efficiently, can simplify human life. However, its negative impacts need to be monitored. The focus of KKN activities in Burni Bius Baru Village includes utilizing technology to bring positive impacts to the quality of life for the local community.